Highly Poison‐Resistant Single‐Atom Co–N4 Active Sites with Superior Operational Stability over 460 h for H2S Catalytic Oxidation. Issue 46 (19th October 2021) - Lei, Ganchang; Tong, Yawen; Shen, Lijuan; Zheng, Yong; Liang, Shijing; Lin, Wei; Liu, Fujian; Cao, Yanning; Xiao, Yihong; Jiang, Lilong
Abstract: Efficient catalytic elimination of hydrogen sulfide (H2 S) with high activity and durability in nature gas and blast‐furnace gas is very critical for both fundamental catalytic research and applied environmental chemistry. Herein, atomically dispersed Co atom catalysts with Co–N4 sites that can transform H2 S into S with conversion rate of ≈100% are designed and prepared. The representative 4Co‐N/NC achieves a sulfur yield of nearly 100% and TOF(Co) of 869 h –1 at 180 °C. Importantly, remarkable long‐term durability is achieved as well, with no obvious loss of catalytic activity in the run of 460 h, outperforming most of the reported catalysts. The short bond length and strong cooperation of Co–N are beneficial to improve the structural stability of the Co–N4 centers, and significantly enhanced resistance of water and sulfation over single‐atom Co‐catalyst. The present mechanism involves the stepwise hydrogen transfer process via the adsorbed *HOO and *HS intermediates. Abstract : Herein, isolated cobalt atoms anchored on a porous tri‐s‐triazine based NC framework are prepared by an efficient synthesis method. The as‐synthesized single‐atom Co–N4 catalysts exhibit remarkable catalytic activity for H2 S selective oxidation. This outcome not only offers a competitive oxidative desulfurization catalyst, but also inspires the fundamental understanding of the underlying structure–activity relationships of the catalysts.